A survey of aldicarb poisoning in dogs and cats in Gauteng and evaluation of the efficacy of hydroxypropyl-β-cyclodextrin as a treatment in aldicarb poisoning - Naidoo, Vinny (University of Pretoria, 2013)
Dissertation (MSc (Paraclinical Sciences))--University of Pretoria, 2005.